Analisis Faktor-Faktor Yang Mempengaruhi Generasi Baby Boomers Menggunakan E-Wallet - Maharani Rona Makom; Alvianita Gunawan Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine and analyze the factors that affect the baby boomers generation using e-wallets. The factors used in this research are Effectiveness, Excellence, and Attractiveness. The population of this study is the Baby Boomers generation whose age is more than 59 years old with a sample of 52 respondents taken from all Baby Boomers generation who use e-wallets in Semarang City with unknown population. The data analysis model uses Multiple Linear Regression Models. The data analysis technique uses the F Statistical Test, t Statistical Test, and the Coefficient of Determination. The results of this study indicate that Effectiveness, Excellence, and Attractiveness simultaneously have a significant effect. Based on the results of the t test, it is concluded that Effectiveness and Excellence have an insignificant effect on E-Wallet user interest, while Attractiveness has a significant effect.